Low temperature rise, high crack resistance concrete and preparation method and application thereof

By adopting specific low-temperature rise and high-crack-resistant concrete formulas, the problem of cracking risk of high-strong volume concrete during construction is solved, and the easy pumping, low-temperature rise, high crack resistance and high durability of concrete is achieved.

CN118754550BActive Publication Date: 2025-04-11WUHAN UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410837138.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-26
Publication Date
2025-04-11
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively solve the problems of high-strength volume concrete in low temperature rise and high crack resistance, which leads to the risk of cracking of concrete during construction.

Method used

A low-temperature rise and high-crack resistance concrete formula is adopted, including cement, aggregate, filler, anti-crack resistance, rheology regulator, vinyl carbonate and sodium hydroxide, and through a specific mixing ratio and stirring and mixing process, concrete with easy pumping, low-temperature rise, high-crack resistance and high durability characteristics are formed.

Benefits of technology

It realizes easy pumpability and high crack resistance of concrete during construction, reduces cracking risks, and improves the durability of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004913487890000101
    Figure BDA0004913487890000101
  • Figure BDA0004913487890000102
    Figure BDA0004913487890000102
  • Figure BDA0004913487890000111
    Figure BDA0004913487890000111
Patent Text Reader

Abstract

The present invention provides a low-temperature rise, high crack resistance concrete and its preparation method and application, which belong to the field of concrete technology. The low-temperature rise, high crack resistance concrete provided by the present invention includes the following raw materials in parts by weight: 250-350 parts of cement, 1500-2500 parts of aggregate, 50-150 parts of filler, 35-45 parts of anti-cracking agent, 30-50 parts of rheology control agent, 5-10 parts of ethylene carbonate and 5-10 parts of sodium hydroxide; wherein the filler includes fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber. The above raw materials work together, in addition to being able to meet the compressive strength of high-strength concrete applications, it also has excellent characteristics such as easy pumping, low temperature rise, high crack resistance and high durability, and can be used for suspension bridges, cable-stayed bridges or cable-stayed-suspension cooperative system bridge box-type structures with a wall thickness greater than 1.5m and a concrete strength grade of C50 or above. High-strength concrete crack control of thick-walled bridge towers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete, and in particular to low-temperature rise and high crack resistance concrete, and a preparation method and application thereof. Background Art

[0002] High-strength concrete refers to concrete with a strength grade of C60 or above, and concrete with a strength grade of C100 or above is called ultra-high-strength concrete. It is made of cement, sand, stone raw materials, water reducer, or fly ash, mineral powder, slag, silica powder and other mixtures, and is produced by conventional processes to obtain high-strength concrete. As a new building material, high-strength concrete has been widely used in high-rise building structures, long-span bridge structures and some special structures due to its high compressive strength, strong deformation resistance, high density and low porosity. The biggest feature of high-strength concrete is its high compressive strength, which is generally 4 to 6 times that of ordinary strength concrete, so the cross-section of the component can be reduced, so it is most suitable for high-rise buildings. Tests have shown that under a certain axial compression ratio and a suitable stirrup ratio, high-strength concrete frame columns have good seismic performance. In addition, the reduction of column cross-section size reduces the deadweight and avoids short columns, which is also beneficial to the seismic resistance of the structure and improves economic benefits.

[0003] However, with the improvement of concrete strength grade, on the one hand, cementitious materials release heat quickly during hydration, increase temperature, and significantly increase shrinkage. The shrinkage and wet deformation are coupled with thermal deformation, further increasing the shrinkage and cracking driving force of the structure. On the other hand, the tension-compression ratio of high-strength concrete decreases, the brittleness increases, and the risk of cracking increases. The existing high-strength concrete preparation technology (high cementitious material dosage, low water-cement ratio) often encounters problems such as high viscosity of concrete mixture, difficult work performance control, high elevation pumping pressure, segregation and pipe blockage during construction. Conventional concrete mix optimization and construction measures include using a low water-cement ratio and adding more fly ash or slag powder to reduce cement dosage, increasing the dosage of cementitious materials in the upper tower column concrete to improve pumping performance, arranging cooling water pipes to reduce the internal temperature of concrete during construction, arranging anti-cracking steel mesh, removing the mold after about 2 days, and using spray curing technology after demolding. The above method can reduce the risk of cracking and the number of cracks, but the amount of cement and cementitious materials used is still too high, the concrete shrinkage is large, and the cracking problem cannot be solved. In other words, it is difficult to solve the shrinkage cracking problem of high-strength high-volume concrete only through temperature control measures.

[0004] The prior art still lacks high-strength volume concrete with better low temperature rise and high crack resistance. Summary of the invention

[0005] The purpose of the present invention is to provide a low temperature rise, high crack resistance concrete and a preparation method and application thereof, which can be used as ultra-high performance concrete to meet the needs of existing construction plans.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a low temperature rise and high crack resistance concrete, comprising the following raw materials in parts by weight:

[0008] 250-350 parts of cement, 1500-2500 parts of aggregate, 50-150 parts of filler, 35-45 parts of anti-cracking agent, 30-50 parts of rheology control agent, 5-10 parts of ethylene carbonate and 5-10 parts of sodium hydroxide;

[0009] The filler includes fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber.

[0010] Preferably, the raw material also includes 100 to 200 parts of water.

[0011] Preferably, the mass ratio of fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber in the filler is 70-90:8-12:3-8:3-8:15-25.

[0012] Preferably, the anti-cracking agent is a temperature-controlled anti-cracking agent.

[0013] Preferably, the rheology control agent contains tannic acid and sodium xylene sulfonate.

[0014] Preferably, the mass ratio of tannic acid to sodium xylene sulfonate in the rheology control agent is 3 to 5:1.

[0015] Preferably, the aggregate includes river sand and crushed stone.

[0016] The present invention also provides a method for preparing the low temperature rise and high crack resistance concrete, comprising the following steps:

[0017] All the raw materials are stirred and mixed to obtain low-temperature-rise and high-cracking-resistant concrete mortar.

[0018] The present invention also provides the application of the low temperature rise and high crack resistance concrete in the construction of super-high bridges.

[0019] Technical effects and advantages of the present invention:

[0020] The low-temperature rise and high crack resistance concrete provided by the present invention includes the following raw materials in parts by weight: 250-350 parts of cement, 1500-2500 parts of aggregate, 50-150 parts of filler, 35-45 parts of anti-cracking agent, 30-50 parts of rheology control agent, 5-10 parts of ethylene carbonate and 5-10 parts of sodium hydroxide; wherein the filler includes fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber. The above raw materials work together, in addition to being able to meet the compressive strength of high-strength concrete applications, it can also achieve better low-temperature rise and high crack resistance. Through the optimal formula provided by the present invention: 52.5P·II cement, fly ash, nano-SiO2, aluminum nitride, wollastonite, carbon fiber, temperature-controlled anti-cracking agent, ethylene carbonate, sodium hydroxide, and a specific rheology control agent are selected as the low-temperature rise and high crack resistance concrete raw materials of the present invention, so that the concrete has excellent characteristics such as easy pumping, low temperature rise, high crack resistance and high durability in practical applications. DETAILED DESCRIPTION

[0021] The present invention provides a low temperature rise and high crack resistance concrete, comprising the following raw materials in parts by weight:

[0022] 250-350 parts of cement, 1500-2500 parts of aggregate, 50-150 parts of filler, 35-45 parts of anti-cracking agent, 30-50 parts of rheology control agent, 5-10 parts of ethylene carbonate and 5-10 parts of sodium hydroxide;

[0023] The filler includes fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber.

[0024] In the present invention, the aggregate may be, for example, silica, quartz, sand, crushed marble, glass balls, granite, basalt, limestone, sandstone, calcite, marble, serpentine, travertine, dolomite, feldspar, gneiss, alluvial sand, any other durable aggregate and mixtures thereof; in the present invention, the aggregate preferably includes river sand and crushed stone.

[0025] In the present invention, preferably, the raw materials also include 100 to 200 parts of water; preferably, the mass ratio of fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber in the filler is 70 to 90:8 to 12:3 to 8:3 to 8:15 to 25; preferably, the anti-cracking agent is a temperature-controlled anti-cracking agent; preferably, the rheology controller contains tannic acid and sodium xylene sulfonate; preferably, the mass ratio of tannic acid and sodium xylene sulfonate in the rheology controller is 3 to 5:1.

[0026] In the present invention, the low temperature rise, high crack resistance concrete may further contain conventional additives used in the prior art, such as grinding aids, strength enhancers, retarders, mechanical reinforcing materials, stabilizers or thickeners, or polymer dispersions in liquid form or solid form (e.g., powder form):

[0027] The grinding aids, such as amines, amino alcohols, glycols, glycol derivatives, glycerol, glycerol derivatives, molasses, corn syrup; the strength enhancer is preferably selected from alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal oxides, alkaline earth metal oxides, alkali metal nitrates, alkaline earth metal nitrates, alkali metal nitrites, alkaline earth metal nitrites, alkali metal thiocyanates, alkaline earth metal thiocyanates, alkali metal halides, alkaline earth metal halides and alkaline earth metal formates;

[0028] The retarder is preferably selected from sucrose, glucose, polymeric sugar and phosphoric acid;

[0029] The mechanical reinforcement material is preferably selected from synthetic polymer fibers (e.g. polypropylene), natural fibers, steel fibers or meshes of these materials;

[0030] The stabilizer or thickener is preferably selected from cellulose ethers and cellulose derivatives, starch, starch ethers and other starch derivatives, xanthan gum, welan gum, dillon gum, high molecular weight polyacrylamide and copolymers thereof containing acrylic acid and / or ATBS;

[0031] The polymer dispersion in liquid form or solid form (e.g. powder form) is preferably selected from polyacrylates, styrene-butadiene copolymers and ethylene-vinyl acetate copolymers;

[0032] In the present invention, the rheology control agent preferably contains tannic acid and sodium xylene sulfonate; in practical applications, if necessary, it can be combined with other types of rheology control agents for use.

[0033] Among the rheology control agents, polycarboxylic acid rheology control agents include polycarboxylic acid ethers, polycarboxylate / crosslinked polymer composites, polycarboxylate / oriented polymer composites, polycarboxylate / highly modified polymer composites, polyether carboxylic acid polymers, maleic acid copolymers, maleate copolymers, maleic acid derivative copolymers, carboxyl-containing polyethers, sulfone-terminated multi-component polymers containing polycarboxylic acids, polycarboxylic acid-based graft copolymers, polycarboxylic acid compounds, and polycarboxylic acid ether polymers. Melamine-based rheology control agents include melamine sulfonic acid-formaldehyde condensates, melamine sulfonate condensates, and melamine sulfonate-polyol condensates. Lignin-based rheology control agents include lignin sulfonates and their derivatives.

[0034] In the present invention, the low temperature rise and high crack resistance concrete may also contain conventional air entraining agents used in the prior art, including anionic surfactants, cationic surfactants, nonionic surfactants and amphoteric surfactants; anionic surfactants are preferably selected from carboxylic acid, sulfate, sulfonic acid and phosphate type surfactants; cationic surfactants are preferably selected from amine salts, primary amine salts, secondary amine salts, tertiary amine salts and quaternary ammonium salt type surfactants; nonionic surfactants are preferably selected from esters, ester-ethers, ethers and alkanolamide type surfactants; amphoteric surfactants are preferably selected from amino acids and sulfobetaine type surfactants.

[0035] In the present invention, the low temperature rise and high crack resistance concrete may also contain conventional defoamers used in the prior art, including oxyalkylene, silicone, alcohol, mineral oil, fatty acid and fatty acid ester defoamers; oxyalkylene defoamers are preferably selected from polyoxyalkylenes such as (poly)oxyethylene-(poly)oxypropylene adducts; (poly)oxyalkylene alkyl ethers such as diethylene glycol heptyl ether, polyoxyethylene oleyl ether, polyoxypropylene butyl ether, polyoxyethylene polyoxypropylene 2-ethylhexyl ether, and oxyethylene oxypropylene adducts of higher alcohols having more than 8 carbon atoms or secondary alcohols having 12 to 14 carbon atoms; (poly)oxyalkylene (alkyl) aryl ethers such as polyoxypropylene phenyl ether and polyoxyethylene nonyl phenyl ether; defoamers prepared by oxyalkylene and acetylenic alcohols such as 2,4,7,9-tetramethyl-5-decyne-4,7-diol, 2,5-dimethyl-3-hexyne-2,5- Acetylenic ethers obtained by addition polymerization of glycol and 3-methyl-1-butyn-3-ol; (poly)oxyalkylene fatty acid esters such as diethylene glycol oleate, diethylene glycol laurate and ethylene glycol distearate; (poly)oxyalkylene sorbitan fatty acid esters such as polyoxyethylene sorbitan monolaurate and polyoxyethylene sorbitan trioleate; (poly)oxyalkylene alkyl (aryl) ether sulfates such as sodium polyoxypropylene methyl ether sulfate and sodium polyoxyethylene dodecylphenol ether sulfate; (poly)oxyalkylene alkyl phosphates such as (poly)oxyethylene stearyl phosphate; (poly)oxyalkylene alkylamines such as polyoxyethylene laurylamine; and polyoxyalkylene amides; the silicone-based defoaming agent is preferably selected from dimethyl silicone oil, silicone paste, silicone emulsion, organically modified polysiloxane (e.g., polyorganosiloxane such as dimethylpolysiloxane), and fluorine-containing silicone oil. The alcohol defoamer is preferably selected from octanol, 2-ethylhexanol, hexadecanol, acetylene alcohol and ethylene glycol; the mineral oil defoamer is preferably selected from kerosene and liquid paraffin. The fatty acid defoamer is preferably selected from oleic acid, stearic acid and its oxyalkylene adduct; the fatty acid ester defoamer is preferably selected from glycerol monoricinoleate, alkenyl succinic acid derivatives, sorbitan monolaurate, sorbitan trioleate and natural wax.

[0036] The present invention also provides a method for preparing the above-mentioned low-temperature rise and high crack resistance concrete, comprising the following steps: stirring and mixing all raw materials to obtain low-temperature rise and high crack resistance concrete mortar; the mixing is preferably carried out using a concrete mixer, and the mixing time is preferably more than 100 seconds.

[0037] The present invention also provides the application of the low-temperature-rise and high-crack-resistance concrete in the construction of super-high bridges, preferably for controlling cracks in high-strength concrete of thick-walled bridge towers with a wall thickness of more than 1.5 m and a concrete strength grade of C50 or above for suspension bridges, cable-stayed bridges or cable-stayed-suspension coordinated system bridge box structures.

[0038] The above-mentioned "super-high bridge construction" mainly has the following difficulties, which lead to the prominent risk of cracking of the main tower concrete and the difficulty of controlling cracking: (1) The wall thickness of the tower column structure is large, the hydration heat of the cementitious material accumulates continuously and is difficult to discharge, and the reinforcement is densely arranged, which makes it difficult to vibrate during pouring. Concrete must have good fluidity to achieve easy compaction. Therefore, the main tower concrete needs to use more cementitious materials to ensure its high-altitude pumping construction performance, which leads to large temperature rise and temperature drop of the concrete and large temperature difference between the inside and outside, and the risk of temperature cracking is prominent; (2) The design strength grade of the main tower concrete is C60. With the increase of the concrete strength grade, on the one hand, the cementitious material hydration heat release is fast, the temperature rises, and the autogenous shrinkage increases significantly. The autogenous shrinkage wet deformation is coupled with the thermal deformation, which further increases the shrinkage cracking driving force of the structure. power; on the other hand, the tension-compression ratio of high-strength concrete decreases, its brittleness increases, and the risk of cracking increases; (3) The main tower column is constructed in multiple sections, and each section is a large-volume structure cast on the lower old concrete. The age difference between the upper and lower tower column sections is generally 7 to 10 days. The old concrete has high strength and fast elastic modulus development. The upper structure is subject to large internal and external constraints, and the tensile stress generated by temperature drop shrinkage and self-shrinkage is large; (4) The main tower is located on the edge of a large river, with open space around it and high wind speed. The construction environment is greatly affected by seasonal climate change. The high-altitude vertical structure concrete of the main tower is extremely difficult to maintain after demolding. Ordinary maintenance measures are basically difficult to play an effective role in this project. The inability to effectively maintain it further exacerbates the risk of cracking of the high-strength, highly constrained, and large-volume concrete of the main tower.

[0039] The above problems can be basically solved by adopting the low temperature rise and high crack resistance concrete provided by the present invention.

[0040] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0041] Example 1

[0042] Low temperature rise, high crack resistance concrete raw material dosage:

[0043] 52.5P·II cement 290kg / m 3、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 10kg / m 3 、Aluminum nitride 5kg / m 3 , Wollastonite 5kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 10kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 、River sand 760kg / m 3 、Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0044] Example 2

[0045] Low temperature rise, high crack resistance concrete raw material dosage:

[0046] 52.5P·II cement 280kg / m 3 、Fly ash 70kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 10kg / m 3 、Aluminum nitride 5kg / m 3 , Wollastonite 5kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 10kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 , river sand 760kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0047] Example 3

[0048] Low temperature rise, high crack resistance concrete raw material dosage:

[0049] 52.5P·II cement 300kg / m 3 、Fly ash 90kg / m 3, Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 10kg / m 3 、Aluminum nitride 5kg / m 3 , Wollastonite 5kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 10kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 , river sand 760kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0050] Example 4

[0051] Low temperature rise, high crack resistance concrete raw material dosage:

[0052] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 12kg / m 3 、Aluminum nitride 8kg / m 3 , wollastonite 3kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 15kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 8kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 , river sand 750kg / m 3 , Crushed stone 1100kg / m 3 , water 130kg / m 3 .

[0053] Example 5

[0054] Low temperature rise, high crack resistance concrete raw material dosage:

[0055] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3, Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 8kg / m 3 , Aluminum nitride 3kg / m 3 , wollastonite 8kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 25kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 12kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 35kg / m 3 , river sand 760kg / m 3 、Crushed stone 1105kg / m 3 , water 140kg / m 3 .

[0056] Example 6

[0057] Low temperature rise, high crack resistance concrete raw material dosage:

[0058] 52.5P·II cement 280kg / m 3 、Fly ash 85kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 10kg / m 3 、Aluminum nitride 5kg / m 3 , Wollastonite 5kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 10kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 , river sand 760kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0059] Example 7

[0060] Low temperature rise, high crack resistance concrete raw material dosage:

[0061] 52.5P·II cement 300kg / m 3 、Fly ash 74kg / m 3, Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 10kg / m 3 、Aluminum nitride 5kg / m 3 , Wollastonite 5kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 21kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 11kg / m 3 , Sodium hydroxide 9kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 、River sand 780kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0062] Example 8

[0063] Low temperature rise, high crack resistance concrete raw material dosage:

[0064] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 12kg / m 3 、Aluminum nitride 8kg / m 3 , wollastonite 3kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 15kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 8kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 、River sand 790kg / m 3 , Crushed stone 1100kg / m 3 , water 130kg / m 3 .

[0065] Example 9

[0066] Low temperature rise, high crack resistance concrete raw material dosage:

[0067] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3, Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 8kg / m 3 , Aluminum nitride 3kg / m 3 , wollastonite 8kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 25kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 12kg / m 3 , sodium hydroxide 8kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4.1:0.9) 42kg / m 3 , river sand 720kg / m 3 、Crushed stone 1085kg / m 3 , water 140kg / m 3 .

[0068] Example 10

[0069] Low temperature rise, high crack resistance concrete raw material dosage:

[0070] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 8kg / m 3 , Aluminum nitride 3kg / m 3 , wollastonite 8kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 25kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 12kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 45kg / m 3 , river sand 760kg / m 3 、Crushed stone 1095kg / m 3 , water 140kg / m 3 .

[0071] Comparative Example 1

[0072] Amount of concrete raw materials:

[0073] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 、Aluminum nitride 15kg / m 3 , Wollastonite 5kg / m3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , Ethylene carbonate 10kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 , river sand 760kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0074] Comparative Example 2

[0075] Amount of concrete raw materials:

[0076] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 10kg / m 3 、Aluminum nitride 5kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 37kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 , river sand 760kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0077] Comparative Example 3

[0078] Amount of concrete raw materials:

[0079] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 30kg / m 3 、Aluminum nitride 5kg / m 3 , Wollastonite 5kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 35kg / m 3 , Ethylene carbonate 10kg / m 3, sodium hydroxide 5kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 4:1) 40kg / m 3 , river sand 760kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0080] Comparative Example 4

[0081] Amount of concrete raw materials:

[0082] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 10kg / m 3 、Aluminum nitride 5kg / m 3 , Wollastonite 5kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Ethylene carbonate 10kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid) 40kg / m 3 , river sand 760kg / m 3 , Crushed stone 1100kg / m 3 , water 135kg / m 3 .

[0083] Comparative Example 5

[0084] Amount of concrete raw materials:

[0085] 52.5P·II cement 290kg / m 3 、Fly ash 80kg / m 3 , Nano-SiO2 (commercially available nano-SiO2, granular, average particle size 20nm) 5kg / m 3 、Aluminum nitride 5kg / m 3 , wollastonite 15kg / m 3 , Carbon fiber (industrial pure, Keda carbon fiber, length 7mm) 20kg / m 3 , Temperature control anti-cracking agent (purchased from Wuhan Sanyuan Special Building Materials Co., Ltd.) 15kg / m 3 , Ethylene carbonate 10kg / m 3 , sodium hydroxide 10kg / m 3 , Rheology control agent (tannic acid: sodium xylene sulfonate = 1:1) 40kg / m 3 、River sand 730kg / m 3, Crushed stone 1300kg / m 3 , water 135kg / m 3 .

[0086] Experimental example

[0087] The performance of the concrete formulas designed in Example 1 and Comparative Examples 1 to 5 was verified, and the control items and indicators are shown in Table 1 below:

[0088] Table 1 Concrete performance standards

[0089]

[0090] Note: The autogenous volume deformation of concrete “+” indicates expansion and “-” indicates contraction.

[0091] The results are shown in Table 2 below:

[0092] Table 2 Test results of each group of concrete

[0093]

[0094]

[0095] Note: The autogenous volume deformation of concrete “+” indicates expansion and “-” indicates contraction.

[0096] It can be seen from the test results that the present invention has designed a set of optimal formulas on the basis of quality control and mix ratio optimization of concrete raw materials, and selected 52.5P·II cement, fly ash, nano-SiO2, aluminum nitride, wollastonite, carbon fiber, temperature-controlled anti-cracking agent, ethylene carbonate, sodium hydroxide, and a specific rheology control agent as the low-temperature rise and high-cracking resistance concrete raw materials of the present invention, so that the concrete has excellent characteristics such as easy pumping, low temperature rise, high crack resistance and high durability in practical applications.

[0097] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A low temperature rise, high crack resistance concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 250-350 parts of cement, 1500-2500 parts of aggregate, 50-150 parts of filler, 35-45 parts of anti-cracking agent, 30-50 parts of rheology control agent, 5-10 parts of ethylene carbonate and 5-10 parts of sodium hydroxide; The filler includes fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber; The mass ratio of fly ash, nano-SiO2, aluminum nitride, wollastonite and carbon fiber in the filler is 70-90:8-12:3-8:3-8:15-25; The rheology control agent consists of tannic acid and sodium xylene sulfonate; The mass ratio of tannic acid to sodium xylene sulfonate in the rheology control agent is 3 to 5:

1.

2. The low temperature rise and high crack resistance concrete according to claim 1, characterized in that: The raw materials also include 100 to 200 parts of water.

3. The low temperature rise and high crack resistance concrete according to claim 1, characterized in that: The anti-cracking agent is a temperature-controlled anti-cracking agent.

4. The low temperature rise and high crack resistance concrete according to claim 1, characterized in that: The aggregate includes river sand and crushed stone.

5. The method for preparing low-temperature rise and high crack resistance concrete according to any one of claims 1 to 4, characterized in that: The following steps are involved: All the raw materials are stirred and mixed to obtain low-temperature-rise and high-cracking-resistant concrete mortar.

6. Use of the low-temperature rise and high crack resistance concrete according to any one of claims 1 to 4 in super-high bridge construction.

Citation Information

Patent Citations

  • Composite expanding agent and application thereof in concrete

    CN118754491A